Sales training: A state of the art and contemporary review - Singh, Vijay Lakshmi (2015)
Organizations of today face numerous challenges, and training their sales force is definitely high on its agenda. This paper endeavors to contribute to the sales training field by providing a comprehensive stateof-the art and contemporary review through the study of publications in sales training research in the last 30 years (1985-2014). The specific objectives of the review are to study the chronological trends and structural distribution of sales training research in terms of the research type, research focus, methods, research themes and other issues such as methodology, analytical techniques, geographical region etc. Findings of 56 articles on sales training research published in the last three decades are analyzed and directions for future research are identified. Doi: http://dx.doi.org/10.1016/j.jefas.2015.01.001